Morphology-dependent catalytic activity of tungsten trioxide (WO3) nanostructures for hydrogenation of furfural to furfuryl alcohol. (17th May 2021) - Ali, Wesam A; Bharath, G; Morajkar, Pranay P; Salkar, Akshay V; Haija, Mohammad Abu; Banat, Fawzi
Abstract: The development of effective and low-cost catalysts for the hydrogenation and stabilization of bio-oils is still a challenge that needs to be overcome. Several nanostructured WO3 catalysts were synthesized in this study to investigate the effect of their morphology on their catalytic activity and selectivity for the hydrogenation of biomass-derived compounds such as furfural (FF). The morphology of the catalysts was tuned via a surfactant-assisted hydrothermal process. Nanorod and nanoprism WO3 catalysts were produced using dodecyl dimethylammonium bromide (DAB) and poly (ethylene-alt-maleic anhydride), respectively, while WO3 nanocubes were produced without the use of surfactants. Various analytical techniques were used to characterize the morphology of the synthesized WO3 catalyst. Furthermore, the hydrogenation of FF was used as a probe reaction to evaluate the catalytic performance of the WO3 nanostructures. Notably, DAB-assisted WO3 nanorods (D-WO3 ) exhibited a relatively high furfuryl alcohol (FFA) selectivity of 85% with an FF conversion of 52% at 100 °C, under 10 bar of H2 pressure over a reaction time of 120 min. A plausible route for the hydrogenation of FF into FFA and other products over D-WO3 nanocatalyst was illustrated. The D-OW3 nanocatalyst's promising results indicate that it could be a viable, low-cost, and efficient alternative catalyst for hydrogenating FF into FFA.